Punitive conscience in the anonymous serial Nurerdin-Kan (1872) - Velásquez Ccosi, Luis Eduardo (2024)
Nurerdin-Kan (1972) is a unique nineteenth-century novel: it is the only fiction of the period that portrays Chinese migration to Peru. Despite this, it has received little attention from national and foreign researchers. This study aims to counteract this undeserved silence, therefore, a meta-critical balance of hermeneutic approaches is made, which, although reduced, outline some important orientations. A theoretical argumentation is also proposed to articulate the analysis and, finally, an interpretation is developed with respect to the enunciative intention of the work, which -although declared by the narrator- contains more nuances than it appears. The main operative concept is that of ‘punitive conscience’, which is deployed throughout the novel as a textual enunciation that suggests new forms of control and surveillance in the social system: the nineteenth-century Peruvian nation.